1983
DOI: 10.1292/jvms1939.45.679
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Rhodococcus equi for mice.

Abstract: Viruleuce of R. equi ATCC 33701 was compared by the intraperitoneal (i.p.) and intravenous (i.v.) routes in mice. Strain ATCC 33701 was more virulent by the i.v. than the i.p. route. The LD50 of strain ATCC 33701 by either route correlated with the initial number of bacteria in the liver and spleen at day 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Nakazawa et al (13) reported the virulence of R. equi for mice and the phagocytosis of four strains of R. equi by cultured murine peritoneal macrophages. They found that there was a significant difference between virulent and less virulent strains in the growth of R. equi in the spleens of intravenously inoculated mice, but not in the rates of phagocytosis (13). Although the strains used differed among these studies, the fate of the bacteria in mice was almost the same except for the rates of phagocytosis by the macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Nakazawa et al (13) reported the virulence of R. equi for mice and the phagocytosis of four strains of R. equi by cultured murine peritoneal macrophages. They found that there was a significant difference between virulent and less virulent strains in the growth of R. equi in the spleens of intravenously inoculated mice, but not in the rates of phagocytosis (13). Although the strains used differed among these studies, the fate of the bacteria in mice was almost the same except for the rates of phagocytosis by the macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The type strain does not cause pneumonia in foals (371,575) and is avirulent in mice (409,577). The virulence of R equi isolates for mice infected intravenously is related to the ability of the isolates to resist clearance from the liver and spleen by resisting phagocytosis and intracellular killing by mouse macrophages (409,577).…”
Section: Pathogenicity Studiesmentioning
confidence: 99%
“…Alveolar macrophages from immunized normal (BALB/c) mice were least effective in killing N. asteroides when compared with macrophages isolated from liver, the peritoneal cavity, and the spleen (9). In studies of mice infected by R. equi by the intravenous, intranasal, or intratracheal route normal mice without genetically defined defects in immune function were used (16,116,165).…”
Section: Natural Infections In Other Speciesmentioning
confidence: 99%
“…The type strain isolated by Magnusson (ATCC 6939, NCTC 1621) does not cause pneumonia in foals (100,163) and is avirulent for mice (116,165). Lethality of strains for mice infected intravenously was related to the ability of organisms to resist both clearance from the liver and spleen and phagocytosis and intracellular killing by mouse macrophages (116,165). Based on data from experimental infections, clinical isolates are more pathogenic than environmental isolates (16,52).…”
Section: Natural Infections In Other Speciesmentioning
confidence: 99%